1989
DOI: 10.1073/pnas.86.4.1105
|View full text |Cite
|
Sign up to set email alerts
|

Model of the interactions of calichemicin gamma 1 with a DNA fragment from pBR322.

Abstract: An analysis of the binding interactions of several DNA-drug complexes that utilize carbohydrates for DNA recognition has been undertaken. It is proposed that the carbohydrate residues function as general minor groove binding elements, and the stereochemistry of aglycone attachment sites is generally disposed to promote a right-handed helical geometry that is complementary to right-handed DNA. The constitution and stereochemistry of the DNA double-strand cleaving agent calichemicin yj is consistent with this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Footprinting studies of calicheamicin g 1 I and its analogs on DNA restriction fragments have established that the sequence specificity of calicheamicin g 1 I for its DNA targets resides within the aryltetrasaccharide component of the drug (Drak et al, 1991;Nicolaou et al, 1992;Aiyar et al, 1994). In addition, the binding and cleavage activities of calicheamicin g 1 I are critically dependent on the presence of guanine residues, and more specifically, their exocyclic amino groups as key DNA recognition elements (Hawley et al, 1989;Li et al, 1994). The binding and cleavage activities of calicheamicin were first investigated at the duplex level (reviewed by Nicolaou & Dai, 1991;Nicolaou et al, 1993) but have been more recently extended to the nucleosomal level (Yu et al, 1995;Li et al, 1995;Kuduvalli et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Footprinting studies of calicheamicin g 1 I and its analogs on DNA restriction fragments have established that the sequence specificity of calicheamicin g 1 I for its DNA targets resides within the aryltetrasaccharide component of the drug (Drak et al, 1991;Nicolaou et al, 1992;Aiyar et al, 1994). In addition, the binding and cleavage activities of calicheamicin g 1 I are critically dependent on the presence of guanine residues, and more specifically, their exocyclic amino groups as key DNA recognition elements (Hawley et al, 1989;Li et al, 1994). The binding and cleavage activities of calicheamicin were first investigated at the duplex level (reviewed by Nicolaou & Dai, 1991;Nicolaou et al, 1993) but have been more recently extended to the nucleosomal level (Yu et al, 1995;Li et al, 1995;Kuduvalli et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…(Walker et al, 1993(Walker et al, , 1994Paloma et al, 1994;Ikemoto et al, 1995) approaches. The first molecular modeling study on the complex emphasized the importance of the stereochemistry at the sugar linkage sites in maximizing the linearity of the aryltetrasaccharide segment and its interaction with the minor groove of the duplex (Hawley et al, 1989). Further, this group suggested that the polarizable iodine substituent on aromatic ring C of calicheamicin g 1 I forms attractive intermolecular contacts with the guanine exocyclic amino groups of the (T-C-C-T)·(A-G-G-A) segment in the bindingsite (Hawley et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Affinity cleavage experiments (7,8) demonstrate that CLM preferentially cleaves DNA at cytosine-containing homopyrimidine tracts, preferentially TCCT. Comparisons of the DNA cleavage specificity of CLM derivatives indicate that the aryltetrasaccharide domain is largely responsible for sequence-specific DNA binding (8,(14)(15)(16)(17)(18) MATERIALS AND METHODS Preparation of Nuclear Extracts and DNA-Bhin Assays. Nuclear extracts were prepared as previously described (19) from TAg Jurkat cells (20) (24), Oct-i (25) and Oct-i-associated protein (OAP) (26), NFKB (27), HNF-1 (28), and Spl (29) was measured by electrophoretic mobility-shift assay.…”
mentioning
confidence: 99%